Capacidades de agir no aplicativo Grindr : agências e negociações diante dos ódios contra homens com práticas afetivo-sexuais gays - Ettore Stefani de Medeiros (2022)
This thesis has as its experience space Grindr, an application used mostly by men who aim to have an affective-sexual relationship with other men. In this technological service, it is common to find people who utter, either on their profiles or via chat, epheminophobic, homophobic, racist, ageist, fatphobic hate speech – among others –,which has generated responses from other users. As discussed by contemporary intellectuals, I understand that contemporary hatred is the antonym of doubt, has an unreflective character and can encompass several layers, from aversions and indifference to complicity. More than that, I argue – mainly from the discussions on agency by Judith Butler and Diego Paz – that there are capacities to act and negotiate in the face of hatred, which can be less or more combative, less or more aligned with normative logics. With this debate on the horizon, I turn my attention to national hatreds linked to homophobia, as it is such a hateful plot that Grindr is linked to. I therefore propose the existence of a national necrobiopolitics in which hatreds against different abject bodies are formulated, including hatreds directed at men who relate affectivelysexually with men. Brazilian necrobiopolitics, overlapping different orders of power, is endowed with historical and sociocultural particularities, which include homophobic and heteronormative logics, present from colonial times to the masculinities of president Jair Bolsonaro. The aforementioned context serves as a foundation for the rationale of the objective of this research: to observe how Grindr end users develop agencies to act in the face of hatred in the application. On an empirical-analytical level, I present profiles collected on Grindr and undertake their study from the concept of agency, which works as an analytical-methodological operator. By noting patterns in the abilities to act present in the profiles, I highlight the three categories of analysis that I arrived at: a) insults as self-denominations, b) (re)appropriation of codes and negotiations with the closet and c) debauched and/or aggressive agencies. In the final considerations, I point out three contributions of this research: a) power and agency, in addition to being interdependent, overlap, b) just as counterpower negotiates with power, power bargains with counterpower, c) necrobiopolitics has as one of its pillars are hatreds, including homophobes. I emphasize that this thesis starts from a nonpositivist perspective, so that the investigation is affiliated with the perspective of affects. In this way, my scientific work is surrounded by affects, experiences, sensations and emotions I have lived, which serve as starting points for both theoretical and empirical reflections.